Odpowiedzi

2010-04-14T22:07:52+02:00
(4-x)2 - (x+1)2 > 5
16 - 8x + x2 - (x2 + 2x + 1) >5
16 - 8x + x2 - x2 - 2x - 1 > 5
-10x > 5 - 16 + 1
-10x > -10
x<1

(x+1)2 - (x-1)2 + (x-1)(x+1) < (1-x)2
x2 + 2x + 1 - (x2 - 2x + 1) + x2 - 1< 1 - 2x + x2
x2 + 2x + 1 - x2 + 2x - 1 + x2 - 1 < 1 - 2x + x2
2x + 2x + 2x < 1 - 1 + 1 + 1
6x < 2
x<1/3

3/4x - 0,75(x - 1)2 + 3/4x2< 0
0,75x - 0,75(x2 - 2x + 1) + 0,75x2 < 0
0,75x - 0,75x2 + 1,5x - 0,75 + 0,75x2 < 0
-0,75x2 + 3x - 0,75 < 0
delta = b2 - 4ac = 3*3 - 4(-0,75)(-0,75) = 9 - 2,25 = 6,75 = 27/4
pierwiastek z delty = pierwiastek z 27/ 2

Obliczasz następnie x1 i x2 z wzorów:
x1 = -b - pierwiastek z delty/ 2a
x2 = -b + pierwiastek z delty/ 2a

Mam nadzieję, że pomogłam:)